Application of Restorative Justice in Narcotics Crimes - Subaidi, Subaidi; Pratita, Afifah Rahma; Ningrum, Anna Cahya; Herawati, Alifah; Kadir, Syukron Abdul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Users or victims of narcotics abuse, which is also a serious crime, have succeeded in coloring the dynamics of people's lives in the country. Users or victims of narcotics abuse continue to increase every year. However, users or victims of narcotics abuse sometimes receive inappropriate treatment which results in stunting in society. thus prompting the author to research how perpetrators or victims of narcotics abuse should be treated. This research is normative research through literature study which is carried out by reviewing and conducting theoretical studies on secondary data sources such as legal materials related to problem formulation, namely statutory regulations, books, journals and other related readings. The data collected is then compiled, studied, then concluded in order to answer the problem formulation mentioned above.